2008
DOI: 10.1182/blood-2008-02-142430
|View full text |Cite
|
Sign up to set email alerts
|

A unique three-dimensional model for evaluating the impact of therapy on multiple myeloma

Abstract: IntroductionHematopoiesis in bone marrow (BM) occurs in distinct microenvironmental niches. Discrete extracellular matrix (ECM) microenvironments within the BM help to separate endosteum, an interface between bone and BM, from the central marrow. Methods for studying hematopoiesis include clonal culture systems in semisolid media, 1 short-term 2 and long-term 3,4 liquid cultures, and tissue culture systems where hematopoietic cells grow on feeder layers of BM stromal cells. 5,6 However, cell culture systems in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
147
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(147 citation statements)
references
References 53 publications
0
147
0
Order By: Relevance
“…Anti-CD47 antibodies inhibited myeloma growth in the presence of a human bone marrow microenvironment The bone marrow microenvironment supports the survival and proliferation of myeloma cells. 2 To determine whether anti-CD47 antibodies also inhibit myeloma growth in the presence of human bone marrow microenvironment, we grafted human fetal bone fragments into immunocompromised mice and directly transplanted patient-derived myeloma cells into the bone grafts. After detecting human immunoglobulin in mouse sera, we treated mice daily with anti-CD47 (B6H12) antibody or PBS for 4 weeks (Figure 4a).…”
Section: Anti-cd47 Antibodies Inhibit the Growth Of Myeloma Cells In mentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-CD47 antibodies inhibited myeloma growth in the presence of a human bone marrow microenvironment The bone marrow microenvironment supports the survival and proliferation of myeloma cells. 2 To determine whether anti-CD47 antibodies also inhibit myeloma growth in the presence of human bone marrow microenvironment, we grafted human fetal bone fragments into immunocompromised mice and directly transplanted patient-derived myeloma cells into the bone grafts. After detecting human immunoglobulin in mouse sera, we treated mice daily with anti-CD47 (B6H12) antibody or PBS for 4 weeks (Figure 4a).…”
Section: Anti-cd47 Antibodies Inhibit the Growth Of Myeloma Cells In mentioning
confidence: 99%
“…[1][2][3] Current myeloma therapies such as hematopoietic cell transplantation and combinatorial chemotherapies are rarely curative and relapse is common. 4 This implies that therapy-resistant myeloma-initiating cells exist and that new therapeutics must be developed to target and eradicate these myeloma-initiating cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several models have illustrated the superior ability of 3D cultures to recreate the BM microenvironment and promote MM cell growth compared to classic 2D cultures. 13,20,21 We have recently shown that a novel 3DTEBM model based on fibrinogen naturally found in the BM supernatant of MM patients recapitulated the pathophysiological environment of MM, recreated the interactions of MM cells with their microenvironment more accurately, allowed the progression of primary patient samples and showed significantly higher resistance to proteasome inhibitors (PIs) compared Figure 1C) or quintuplicates (Figure 1Bi, Figure 1Biii) and each experiment was repeated 3 times. Results are shown as mean ± standard deviation and analyzed using two-way ANOVA for statistical significance, and were considered significantly different for P value less than 0.05.…”
Section: Stromal Cell Lines (Hs-5 Hs-27a and Msp-1) (5 -20×10mentioning
confidence: 99%
“…In a later study utilizing methylcellulose media supplemented with lymphocyte conditioned media as growth factors, clonogenic MM progenitor cells were found in BM cells lacking expression of the plasma cell marker CD138. [11][12][13][14][15] It was further reported that rituximab inhibited MM colony formation 11 and that CD20 þ B cells from some MM patients could produce MM plasma cells in a 3-D culture in vitro, 16 which suggests that CD138…”
Section: Introductionmentioning
confidence: 99%